(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Choledochal cyst (CC) is a rare congenital abnormality of the biliary tract, for which there is no standardized surgical treatment. If left untreated it may cause bile duct (BD) obstruction to cholangiocarcinoma. For the commonest type of Choledochal cyst (Type I and IV) the treatment is surgery, although, the reconstruction technique of the BD has no gold standard. Objective: To assess the outcome of surgical treatment of choledochal cyst in pediatric cases in 8 years period in CMH Dhaka, a tertiary referral hospital of Bangladesh Armed Forces. Materials and Methods: This cross sectional study was carried out in the department of Paediatric Surgery at CMH Dhaka on 20 children of under 10 years having choledocal cysts. The study period was from March 2006 to February 2014. Results: Total of twenty patients aged 3 years to 10 years was included in the study. Out of them 14(70%) were females and 6(30%) were males. Fifteen (75%) patients presented with recurrent abdominal pain, 14(70%) with recurrent jaundice, 4(20%) patients with abdominal mass as initial symptoms. Twelve (60%) patients were diagnosed by Ultrasonogram (USG), rests were by Contrast Enhanced Computed Tomography (CECT) and Magnetic Resonance Cholangiopancreatography (MRCP). Eighteen patients presented with type 1 choledochal cyst and 2 of them had type IV choledochal cyst. All the patients were submitted to cyst excision and Roux-en-Y hepaticojejunostomy. Among them one patient required refashioning of anastomotic site to treat bile leakage. Conclusion: Early diagnosis and referral is essential to prevent complications and grave consequences and prognosis of these cases after surgery is good. Journal of Armed Forces Medical College Bangladesh Vol.12(2) 2016: 117-121